Caracterización de una colección de Theobroma cacao L. en Tingo María usando marcadores moleculares ISSR - Chia W., Julio; Garcia C., Luis; Suni N., Mery; Eskes, Bertus (Aporte Santiaguino, 2011)
Cacao breeding programs focus in obtaining cacao varieties with important traits to both producers and consumers. A vital step for plant breeders is the characterization of the genetic material kept in germplasm banks in order to describe its level of diversity, and find interesting traits both morphologically and molecularly. In this way, the investigator will monitor how useful the accessions could be, determine duplications, and manage the bank appropriately. In this study, we aimed to test: the potential of ISSR (Interspread Sequence Repeats) markers to differentiate 46 cacao accessions maintained in Tingo Maria - Perú, and the similarity relationships between the accessions. In this research, the results showed that ISSR, despite its dominance nature, could establish eye-catching associations, such as, the grouping of Trinitario accessions into a common cluster